Lower urinary tract symptoms and metabolic disorders: ICI‐RS 2014. Issue 2 (February 2016) - Denys, Marie‐Astrid; Anding, Ralf; Tubaro, Andrea; Abrams, Paul; Everaert, Karel
Abstract : Aims: To investigate the link between lower urinary tract symptoms (LUTS) and metabolic disorders. Materials and Methods: This report results from presentations and subsequent discussions about LUTS and metabolic disorders at the International Consultation on Incontinence Research Society (ICI‐RS) in Bristol, 2014. Results: There are common pathophysiological determinants for the onset of LUTS and the metabolic syndrome (MetS). Both conditions are multifactorial, related to disorders in circadian rhythms and share common risk factors. As in men with erectile dysfunction, these potentially modifiable lifestyle factors may be novel targets to prevent and treat LUTS. The link between LUTS and metabolic disorders is discussed by using sleep, urine production and bladder function as underlying mechanisms that need to be further explored during future research. Conclusion: Recent findings indicate a bidirectional relationship between LUTS and the MetS. Future research has to explore underlying mechanisms to explain this relationship, in order to develop new preventive and therapeutic recommendations, such as weight loss and increasing physical activity. The second stage is to determine the effect of these new treatment approaches on the severity of LUTS and each of the components of the MetS. Neurourol. Urodynam. 35:278–282, 2016 . © 2016 Wiley Periodicals, Inc.